2007
DOI: 10.1007/s10577-007-1125-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of cross-species in-situ hybridization (ZOO-FISH) to assess chromosome abnormalities in day-6 in-vivo- or in-vitro-produced sheep embryos

Abstract: Causes of chromosomal differences such as mosaicism between embryos developed in vivo and in vitro may be resolved using animal models to compare embryos generated in vivo with those generated by different production systems. The aims of this study were: (1) to test a ZOO-FISH approach (using bovine painting probes) to detect abnormal chromosome make-up in the sheep embryo model, and (2) to examine the extent of chromosome deviation in sheep embryos derived in vivo and in vitro. Cytogenetic analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
1
20
0
1
Order By: Relevance
“…Co-culture systems in sheep and goat are usually based on including oviductal cells in TCM-199 medium. Semi-defined medium is also used often in small ruminant IVC based on the components of the sheep oviductal fluid (SOF), a medium containing essential and non-essential amino acids supplemented with BSA [48,43]. In our laboratory, sheep embryos cultured in SOF medium supplemented with amino acids and BSA at 38°C in 5% O2, 5% CO2, 90% N2 humidified atmosphere resulted in 19.2% blastocyst rates from total oocytes cultured [43].…”
Section: In Vitro Culturementioning
confidence: 93%
See 4 more Smart Citations
“…Co-culture systems in sheep and goat are usually based on including oviductal cells in TCM-199 medium. Semi-defined medium is also used often in small ruminant IVC based on the components of the sheep oviductal fluid (SOF), a medium containing essential and non-essential amino acids supplemented with BSA [48,43]. In our laboratory, sheep embryos cultured in SOF medium supplemented with amino acids and BSA at 38°C in 5% O2, 5% CO2, 90% N2 humidified atmosphere resulted in 19.2% blastocyst rates from total oocytes cultured [43].…”
Section: In Vitro Culturementioning
confidence: 93%
“…It is obvious that artificial oocyte maturation and culture systems have detrimental effects on embryo development compared to their in vivo counterparts. Recent fluorescent in situ hybridization cytogenetic studies from our laboratory using whole chromosome painting probes have revealed that high incidence of chromosomal abnormalities in sheep blastocysts derived from IVP systems, compared to in vivo derived blastoctsts [43] emphasizing the inherent differences in the two production methods.…”
Section: Speciesmentioning
confidence: 99%
See 3 more Smart Citations